Corrigendum: Telmisartan Prevents Alveolar Bone Loss by Decreasing the Expression of Osteoclasts Markers in Hypertensive Rats With Periodontal Disease (Front. Pharmacol., (2020), 11, (579926), 10.3389/fphar.2020.579926) - Brito, Victor Gustavo Balera [UNESP]; Patrocinio, Mariana Sousa [UNESP]; Linjardi, Maria Carolina [UNESP]; Emanuelli Alves Barreto, Ayná [UNESP]; Frasnelli, Sabrina CT [UNESP]; Lara, Vanessa; Santos, Carlos Ferreira; Oliveira, Sandra Helena Penha [UNESP] (Frontiers, 2021)
In the original article, there was a mistake in Figure 3 as published. On Figure 3 panel F, an error was made when assembling the representative imagens on the board, and the same image was included twice for the SHR Control group and SHR Telm + PD group. The correct representative image for the SHR Control group was included and the corrected Figure 3 appears below. The authors apologize for these errors and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. (Figure presented.).
Keywords: AT1 blocker; bone metabolism; cytokines; osteoblast; osteoclast; periodontal disease; spontaneous hypertensive rats; telmisartan